Evaluating the Impact of Price Caps - Evidence from the European Roam-Like-at-Home Regulation - Giulia Canzian; Gianluca Mazzarella; Frank Verboven; Stefano Verzillo; Louis Ronchail (Center for Economic Studies and ifo Institute (CESifo), 2021)
The roam-like-at-home regulation (RLAH) eliminated all mobile roaming surcharges to Eu-ropean consumers travelling within the European Economic Area (EEA). We measure the causal impact of the regulation on EEA roaming traffic, using the Rest of the World as a control group. We find large and heterogeneous effects on retail and wholesale traffic volumes and revenues. To evaluate the welfare effects of the regulation, we develop a framework that includes consumer surplus, retail and wholesale profits. The gains in consumer surplus are large, and mainly stem from data services. The consumer gains are proportionately larger in small, open economies and in countries with previously high roaming prices. Finally, total welfare increases considerably, because the consumer surplus gains far outweigh profit losses. As such, the removal of market power more than compensates for a distortion from a possible overconsumption at zero surcharges.
Keywords: L13; L51; L96; 330; price caps; international roaming; mobile telecom; market integration